Are hedge funds' charitable donations strategic? - Vikas Agarwal; Yan Lu; Sugata Ray (University of Cologne, Centre for Financial Research (CFR), 2020)
We study whether hedge funds make charitable donations to further their business interests. We find that donations are driven by poor fund flows and performance. Post-donation, donor funds experience lower outflows compared to matched non-donors. One-off donations and donations to charities which hold fundraising events catering to the hedge fund community are more likely to mitigate outflows after poor performance. These findings are consistent with strategic motivations driving at least some donations. While the economics of donations initially appear quite favorable to the hedge funds, the benefits from donations are not scalable. Moreover, investors punish donors through greater redemptions if poor performance persists post-donation.
Keywords: D64; G23; G41; 330; Hedge funds; Philanthropy; Trust; Charitable Donations; Capital Formation; Corporate Social Responsibility (CSR)